COMPUTER-ASSISTED LONGITUDINAL SURVEYS DESIGN AND IMPLEMENTATION. - CAPILUPPI, Claudio (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2008)
In the social research field, the longitudinal method is used when the study is about the evolution of a time dependent phenomenon. In longitudinal surveys, the same subjects are followed across time detecting changes on their measured variables, by means of a questionnaire that can be dependent on time and historical data of each subject. Time dependent interviewing is one of the main focus in longitudinal surveys, but it is very difficult to implement in practice by paper and pencil interviewing. The introduction of CAI (Computer-Assisted Interviewing) in longitudinal surveys promises to revolution this field of surveys, making actually possible to implement advanced interviewing techniques by using individual historical data. In this paper we discuss about the technological support required in order to implement longitudinal surveys with intensive time dependent interviewing, and suggest some solutions for a CAI system with full longitudinal support.